When do employees leave their job for entrepreneurship: Evidence from linked employer-employee data - Ari Hyytinen; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2006)
Existing firms are argued to be an important source of new entrepreneurs. Yet, relatively little is known about the characteristics of firms that breed new entrepreneurs. We use a large linked employee-employer dataset to trace and characterize the types of firms from which new entrepreneurs come in Finland. We find evidence for entrepreneurial learning in smaller firms, for they spawn new entrepreneurs more frequently than larger firms. We also find that the productivity of firms and their R&D-intensity are negatively related to the probability that employees transit into entrepreneurship. These results are robust to controlling for a number of employee and employer attributes.
Keywords: G14; G31; G32; 330; entrepreneurship; occupation choice; mobility; Arbeitsmobilität; Arbeitskräfte; Selbstständige; Betriebsgröße; Wirtschaftlichkeit; Betriebliche Forschung; Finnland